2014
DOI: 10.11648/j.avs.20140203.15
|View full text |Cite
|
Sign up to set email alerts
|

Response of Broiler Chicken to Diets Containing Different Mixture Powder Levels of Red Pepper and Black Pepper as Natural Feed Additive

Abstract: The effect of feeding different mixture powder levels of red and black pepper as natural feed additives on productive performance, carcass characteristics and economical efficiency were studied. A total of one hundred and sixty one-day old, unsexed (Ross-308) broiler chicks were randomly divided into four experimental groups. Each group was further subdivided into five replicates at the rate of eight chicks per pen in complete randomized design. The birds were fed on two basal diets (starter and finisher diet)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Although, during the 6 th week feed conversion efficiency was numerically higher compared to other weeks. The results were in agreement with the findings of Shahverdi et al (2013);Tazi et al (2014); Ghaedi et al (2013); Mohamed et al (2014) and Rahimian et al (2016) who observed that the feed conversion efficiency was significantly higher on black pepper supplemented diet as compared to control group. The variations in the result might be due to the levels of use in the diet and species differences of broiler birds and agro-climatic conditions of the study area.…”
Section: Feed Intakesupporting
confidence: 92%
See 2 more Smart Citations
“…Although, during the 6 th week feed conversion efficiency was numerically higher compared to other weeks. The results were in agreement with the findings of Shahverdi et al (2013);Tazi et al (2014); Ghaedi et al (2013); Mohamed et al (2014) and Rahimian et al (2016) who observed that the feed conversion efficiency was significantly higher on black pepper supplemented diet as compared to control group. The variations in the result might be due to the levels of use in the diet and species differences of broiler birds and agro-climatic conditions of the study area.…”
Section: Feed Intakesupporting
confidence: 92%
“…The average mortality, liveability (%) and performance index (PI) from day old to six weeks of age are given below from the above table 1, it was observed that there was no mortality from day one till the end of the experiment. Similar findings were found by other workers Tazi et al, (2014) and Chuparan et al, (2016) who reported that there was no significant difference with the supplementation of black pepper in broiler diet as compared to control group. The values of performance index were recorded as 409.85, 373.91, 402.77 and 387.54 for T1, T2, T3 and T4 respectively.…”
Section: Mortality/liveability and Performance Indexsupporting
confidence: 91%
See 1 more Smart Citation
“…The role of piper nigrum in increasing the production of digestive enzymes may be due to stimulate the liver to produce acids and salts in gall bladder, which further digests food ingredients. In partially agreement,Mohamed and El-Tazi (2014) found that FI and FCR were increased with increasing the mixture level of black and red peppers.…”
mentioning
confidence: 52%
“…In agreement with our results, although in different species, capsaicin supplementation at 150 ppm increased body weight gain in Pekin ducks [ 38 ]. El-Tazi [ 39 ] also reported that 0.5%, 0.75% and 1% capsaicin inclusion in broiler chicks’ diet improved body weight gain and feed conversion ratio. This could be due to the antimicrobial properties of capsaicin that alleviate harmful microbes in the gastrointestinal tract to improve epithelial integrity, such as an increase in the mucosa and sub-mucosa thickness of the small intestine and absorption surface [ 40 , 41 ].…”
Section: Discussionmentioning
confidence: 99%